Construction safe design approach / Asmalia Che Ahmad ... [et al.] - Che Ahmad, Asmalia; Bahari, Ismail; Mohd Zain, Muhammad Fauzi; Mat Piah, Omar (2012)
Safe design approach is a new scenario in Malaysia. In common practice, construction safety is only emphasized during the construction phase. Hence, the most effective method in enhancing construction safety during design phase was not realised. Developed countries have practiced construction safe design to boost their safety level. Lack of awareness and the involvement of construction satakeholders in safe design practices have caused this approach to be marginalized. This study was conducted to determine the level of awareness on construction safe design among Malaysian professionals. Additionally, this study also identifies the party that should play key role in implementing this approach. Questionnaires were used as research instrument. 295 construction professionals were identified as respondents in this study by the chosen purposive sampling technique. From the analysis, the awareness level among the construction professionals was at moderate level. The authorities were identified as the parties that should play the central role in implementing this approach comprehensively.